Identifying relevant factors about work accidents in the road transport sector and the deaths relation in this scenario - Lucimara Ferreira da Silva; Beatriz Lavezo dos Reis; Liandra Dos Santos Jesus; Gislaine Camila Lapasini Leal; Edwin Vladimir Cardoza Galdamez (Dyna, 2023)
Workers’ health and safety are a major concern in society, since work accidents have a major impact on productivity and economy. In Brazil, the accidents are officially reported through Work Accident Communication and they are available to the public. Thus, this study analyzed a balanced dataset containing 1,206 records of deaths caused by work accidents related to the transport sector. Its aim was analyzing how the deaths in the transport sector are related with the other work accident factors. To achieve this goal, twelve performance data mining techniques are compared, through five performance metrics, regarding the predictive capacity of the occurrence of deaths caused by work accidents. In this context, the XGBoost and Naïve Bayes algorithms showed the best predictive capacity. The explanatory analysis indicates that work accidents followed by death in road transport are predictable due to the severity of the injuries and vital parts of the body are affected.